"Tourism, water, and gender"—An international review of an unexplored nexus. (29th April 2020) - Cole, Stroma K. G.; Mullor, Ernest Cañada; Ma, Yue; Sandang, Yesaya
Abstract: This international literature review of the tourism–water nexus identifies a gender gap. Tourism development can affect water supply both quantitatively and qualitatively. Many regions will face considerable problems of water availability and quality, affecting their tourism sector and increasing competition with local residents, and other industries especially agriculture. This international review of literature explores the tourism–water nexus, comparing and contrasting literature published in English, Chinese, and Spanish. Securing access to safe water for continued tourism development is a common theme and the vast majority of work has focused on hotels including water pricing, water‐saving practices and innovative management methods. In all continents, struggles are apparent, and the unsustainability of tourism is having impacts on water quantity and quality. This article identifies significant gaps in the literature including climate change, the energy‐water nexus, and the links with the Sustainable Development Goals. Furthermore, studies from a gendered perspective are minimal and the potential for areas of further gendered studies within the tourism–water nexus are highlighted including intersectionality, water insecurity and sanitation, tourism and gender based violence, and additional unpaid care work. This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance Human Water > Rights to Water Abstract : André Bazán's mural of the community/tourism water conflict in Playa Potrero, Guanacaste, Costa Rica.